2022
DOI: 10.1039/d2nh00143h
|View full text |Cite|
|
Sign up to set email alerts
|

Single atomic Fe–N4 active sites and neighboring graphitic nitrogen for efficient and stable electrochemical CO2 reduction

Abstract: Single atomic Fe–Nx moieties have shown great performance in CO2-to-CO conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Moreover, single Fe atoms can also significantly increase the CO 2 RR activity ( Figure 5C ). Tang et al reported an atomically dispersed Fe-coordinated N-doped carbon catalyst that enhanced CO 2 reduction to produce CO with high activity ( Takele Menisa et al, 2022 ). The neighboring graphitic N transferred more electrons to the intermediate COOH*, increasing COOH* adsorption strength.…”
Section: Applications Of Sacs For Co 2 Rrmentioning
confidence: 99%
“…Moreover, single Fe atoms can also significantly increase the CO 2 RR activity ( Figure 5C ). Tang et al reported an atomically dispersed Fe-coordinated N-doped carbon catalyst that enhanced CO 2 reduction to produce CO with high activity ( Takele Menisa et al, 2022 ). The neighboring graphitic N transferred more electrons to the intermediate COOH*, increasing COOH* adsorption strength.…”
Section: Applications Of Sacs For Co 2 Rrmentioning
confidence: 99%
“…The findings of Zhang et al were confirmed by the works of Zhu et al 227 The latter also observed that graphitic N further improved the catalytic performance of Fe–N 4 sites by lowering the free energy of the formation of the *COOH intermediate. Takele Menisa et al 223 also attribute the efficient electrochemical CO 2 reduction of FeN 4 C to the presence of the neighboring graphitic nitrogen. The group reports that the increase in the number of neighboring graphitic nitrogen decreases the number of electrons transferred between *CO and the catalyst, which reduces the energetic barrier for the desorption of *CO.…”
Section: Sacs For Electrochemical Co2rr To Comentioning
confidence: 99%
“…After this, the research of SAC has been continuously developed. At present, the commonly synthetic methods include the impregnation method, [ 22,23 ] high‐temperature pyrolysis method, [ 24,25 ] atomic layer deposition (ALD) method, [ 26–28 ] coprecipitation method, [ 29,30 ] etc. However, Pt resources are scarce and expensive, which makes it impossible for Pt SACs to achieve large‐scale commercial applications.…”
Section: Introductionmentioning
confidence: 99%